Smart museums: enjoying culture virtually Case of Virtual Museum of the National Museums Foundation. Rabat - Morocco - Ikrame SELKANI (Smart Cities and Regional Development Journal)
Before, the city was a space dedicated to offering a range of services to all the inhabitants who lived there, such as public transportation, education, housing.... However, things have undergone a certain change with the introduction of the Internet and ICTs. To this end, we have today began to hear about -Smart City-this new emerging concept leaves no major metropolis untouched. The digital and modern age has affected almost every sector, even those who imagined they were frozen in time, thanks to the cities have experienced the technologies were throughout the early 21st century. Here, we cite for example: the world of banks, telecommunications, service companies ... even the public sector such as: education, culture, administration. Future museums may also contribute to human culture in a society witnessing rapid changes via smart museum technology that encourages constructive participation with the public. Digital technologies did not emerge overnight in museums and started by replacing conventional analog broadcasting media without altering the experience of visitors. What is really new is the appearance, which includes screens near the works giving more information. The term "virtual museum" has been defined as follows: "... a collection of digitized objects logically articulated and composed of various supports which, due to its connectivity and character multi-access, allow you to transcend traditional modes of communication and interaction with the visitor... ". Our study case will also reach the Virtual Museum of the National Museums Foundation Rabat Morocco. Here, we will discover the exhibits the Virtual Museum in partnership with Virtuelli, a virtual imaging agency which is a platform, open to the general public and art lovers that hosts virtual tours of art exhibitions organized by the National Foundation of Museums under its supervision.